Innate immunity and microbial dysbiosis in hidradenitis suppurativa – vicious cycle of chronic inflammation - Chopra, Divya; Arens, Rachel A.; Amornpairoj, Watcharee; Lowes, Michelle A.; Tomic-Canic, Marjana; Strbo, Natasa; Lev-Tov, Hadar; Pastar, Irena (Frontiers in Immunology, 2022)
Hidradenitis Suppurativa (HS) is a chronic multifactorial inflammatory skin disease with incompletely understood mechanisms of disease pathology. HS is characterized by aberrant activation of the innate immune system, resulting in activation of pathways that aim to protect against pathogenic microorganisms, and also contribute to failure to resolve inflammation. Imbalance in innate immunity is evident in deregulation of host antimicrobial peptides (AMPs) and the complement system associated with the microbiome dysbiosis. The pathology is further complicated by ability of pathogens associated with HS to overcome host immune response. Potential roles of major AMPs, cathelicidin, defensins, dermcidin, S100 proteins, RNAse7, and complement proteins are discussed. Dysregulated expression pattern of innate immunity components in conjunction with bacterial component of the disease warrants consideration of novel treatment approaches targeting both host immunity and pathogenic microbiome in HS.